THE IMPLEMENTATION OF MURABAHAH CONTRACT ON THE RETIREMENT FINANCING AT SHARIA BANK OF INDONESIA - Alazhari, Alvionita Ardilla; B, M Taufan; Amelia, Yuni (Tadayun: Jurnal Hukum Ekonomi Syariah, 2023)
Retirement financing has a small financing risk because retirement financing at the Sharia Bank of Indonesia is based on a cooperation agreement between the Sharia Bank of Indonesia and retirement fund management institutions such as PT Taspen. One Sharia-based financing product in demand is selling and purchasing products with the Murabahah contract. The concept and application of financing with a Murabahah contract that is simple and easy to handle in the administration of Islamic banks is the main factor of Islamic banks in Indonesia applying the principle of Murabahah in financing. This research is doctrinal legal research, usually called normative legal research, supported by empirical data. In this research, the researcher found that the mechanism of retirement financing begins with the financing submission by the customer to the Bank, checking data/verifying data, analysis of financing feasibility, evaluation of financing needs and decisions, administration and accounting of financing, and the realization of the funding. Constraints in using Murabahah contract on retirement financing product at Sharia Bank of Indonesia Palu Basuki Rahmat as customers do not want to be complicated by the administrative process because of the age factor, which is the retirement age. Abstrak Pembiayaan pensiun merupakan pembiayaan yang memiliki risiko pembiayaan yang kecil, karena pembiayaan pensiun di Bank Syariah Indonesia didasarkan pada perjanjian kerjasama antara Bank Syariah Indonesia dengan lembaga pengelola dana pensiun seperti PT Taspen. Salah satu produk pembiayaan berbasis syariah yang cukup diminati adalah produk jual beli dengan akad Murabahah. Konsep dan aplikasi pembiayaan dengan akad Murabahah yang sederhana dan mudah dalam penanganan administrasi bank syariah menjadi faktor utama bank syariah di Indonesia menerapkan prinsip Murabahah dalam pembiayaannya. Penelitian ini merupakan penelitian hukum doktrinal atau biasa disebut penelitian hukum normatif yang didukung data empiris. Dalam penelitian ini, peneliti menemukan mekanisme pembiayaan pensiun diawali dengan pengajuan pembiayaan oleh nasabah kepada bank, pengecekan data/verifikasi data, analisis kelayakan pembiayaan, evaluasi kebutuhan dan keputusan pembiayaan, administrasi dan pembukuan pembiayaan, dan realisasi pembiayaan. Kendala dalam penggunaan akad murabahah pada produk pembiayaan pensiun di Bank Syariah Mandiri Palu Basuki Rahmat adalah karena nasabah tidak ingin dipersulit dengan proses administrasi karena faktor usia, yaitu usia pensiun.